2021
DOI: 10.48550/arxiv.2111.12708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Planet Detection with Disk Modeling: Keck/NIRC2 Imaging of the HD 34282 Single-armed Protoplanetary Disk

Juan Quiroz,
Nicole L. Wallack,
Bin Ren
et al.

Abstract: Formed in protoplanetary disks around young stars, giant planets can leave observational features such as spirals and gaps in their natal disks through planet-disk interactions. Although such features can indicate the existence of giant planets, protoplanetary disk signals can overwhelm the innate luminosity of planets. Therefore, in order to image planets that are embedded in disks, it is necessary to remove the contamination from the disks to reveal the planets possibly hiding within their natal environments… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Both features have been seen in scattered light observations of the HD 34282 disk (Fig. 7), which has a one-armed spiral with a shadowed region on the outside (de Boer et al 2021;Quiroz et al 2021). The HD 34282 disk also harbors a mm continuum emission clump at roughly the same location as the one-armed spiral (left panel in Fig.…”
Section: Summary and Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Both features have been seen in scattered light observations of the HD 34282 disk (Fig. 7), which has a one-armed spiral with a shadowed region on the outside (de Boer et al 2021;Quiroz et al 2021). The HD 34282 disk also harbors a mm continuum emission clump at roughly the same location as the one-armed spiral (left panel in Fig.…”
Section: Summary and Discussionmentioning
confidence: 61%
“…7 we compare the SPHERE NIR scattered light image of the disk with our model image at the same viewing angle. A one-armed spiral (feature B1 in de Boer et al 2021;Quiroz et al 2021) has been identified in the HD 34282 disk. The feature appears similar to the vortex in our model.…”
Section: Resultsmentioning
confidence: 99%